(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This scientific thesis provides an in-depth analysis of the strategic role of aliphatic amines in the modern chemical industry and technological processes, their diverse practical applications across the national economy, the fundamental principles of industrial-scale synthesis technologies based on paraffin hydrocarbons, process kinetics, and the influence of catalytic systems on selectivity. The study examines the relationship between the structure of heterogeneous catalysts, activation energy, and reaction mechanisms in improving product yield, and further addresses the technical and economic aspects of establishing the production of high-molecular-weight amines from local raw materials — namely, the paraffin fractions of the Shurtan and Muborak oil-and-gas chemical complexes. The growth dynamics of the global amine market and Uzbekistan’s import-substitution potential in the chemical industry are considered separately.